Not Hockey Critical Essays on Canada's Other Sport Literature - Abdou, Angie; Dopp, Jamie (Athabasca University Press, 2023)
In this carefully curated collection of essays, editors Jamie Dopp and Angie Abdou go beyond their first collection, Writing the Body in Motion, to engage with the meaning of sport found in Canadian sport literature. How does "sport" differ from physically risky recreational activities that require strength and skill? Does sport demand that someone win? At what point does a sport become an art? With the aim of prompting reflections on and discussions of the boundaries of sport, contributors explore how literature engages with sport as a metaphor, as a language, and as bodily expression. Instead of a focus on what is often described as Canada's national pastime, contributors examine sports in Canadian literature that are decidedly not hockey. From skateboarding and parkour to fly fishing and curling, these essays engage with Canadian histories and broader societal understandings through sports on the margin. Interspersed with original reflections by iconic Canadian literary figures such as Steven Heighton, Aritha Van Herk, Thomas Wharton, and Timothy Taylor, this volume is fresh and intriguing and offers new ways of reading the body.